EXPLORING THE LINK BETWEEN SEXUAL KNOWLEDGE AND ATTITUDES TOWARD SEXUAL BEHAVIOR AMONG ADOLESCENTS IN BOGOR, INDONESIA - Dely Maria, Triana Indrayani (South Eastern European Journal of Public Health, 2025)
Background: Adolescents in Indonesia are increasingly exposed to sexual information through media and peer interactions, leading to greater sexual knowledge. However, the relationship between sexual knowledge, attitudes, and sexual behavior remains complex, particularly within Indonesia's conservative cultural context, which does not support LGBT practices. Understanding these relationships is vital for developing sexuality education programs aligned with societal values. Objective: This study aims to examine the direct and indirect relationships between sexual knowledge, attitudes toward sexual behavior, and sexual behavior among adolescents in Bogor, Indonesia. Method: A cross-sectional quantitative study was conducted with 257 11th-grade students from public senior high schools (SMAN) in Bogor and Cibinong. Data were collected through structured questionnaires and analyzed using path analysis. Result: Sexual knowledge had a significant direct relationship with sexual behavior (p < 0.05), indicating that increased knowledge was associated with greater sexual activity. However, the relationship between sexual knowledge and attitudes was not significant (p > 0.05), suggesting that knowledge did not necessarily alter attitudes. Attitudes were significantly associated with sexual behavior (p < 0.05), but this relationship was weak. The indirect effect of sexual knowledge on behavior through attitudes was not significant. Conclusion: Sexual knowledge directly influences adolescent sexual behavior but does not significantly affect attitudes. Attitudes have a weak influence on behavior. These findings suggest that sexuality education in Indonesia should not only enhance knowledge but also emphasize moral and cultural values consistent with societal norms that do not support LGBT practices. Family and community involvement is crucial to fostering responsible sexual behavior among adolescents.